Ninth International Conference of Historical Geographers, Pre-conference Symposium on ‘Identity and Landscape’, 28-30 June 1995, Singapore - Yeoh, Saw Ai Brenda (Wiley, 2014)
10.1111/j.1467-9493.1995.tb00079.x